Assessing Function Modeling Frameworks: Technical Advantage Predictions as a Conceptual Tool. Issue 3 (2nd September 2021) - van Eck, Dingmar; Weber, Erik
Abstract : While function modeling has been around in engineering design research since the 1960s, there have been no systematic, comparative studies devoted to assessing the adequacy of function modeling frameworks in light of engineering design objectives. This systematic assessment and comparison – called benchmarking – is now recognized as a central research issue in current function modeling research, but insight into how this benchmarking can be done is at present limited. In this paper, we attempt to improve our insight into how benchmarking can be done for a specific but important engineering context: function optimization of reverse-engineered systems. We argue that the capacity to produce technical advantage predictions, viz. predictions concerning the improved functional performance of a redesigned technical system, is an important benchmark criterion in this context. We subsequently illustrate the utility of the criterion by assessing two prominent function modeling frameworks in terms of it. Throughout the paper, we use a case study of the design of an electric wok to clarify and illustrate our ideas.